1994
DOI: 10.1083/jcb.127.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of chemoattractant-induced changes in [Ca2+]i and cell shape, polarity, and locomotion by InsP3, DAG, and protein kinase C in newt eosinophils.

Abstract: Abstract. During chemotaxis large eosinophils from newts exhibit a gradient of [Ca2+]i from rear to front.The direction of the gradient changes on relocation of the chemoattractant source, suggesting that the Ca 2+ signal may trigger the cytoskeletal reorganiTation requlred for cell reorientation during chemotaxis. The initial stimulatory effect of chemoattractant on [Ca2+]i and the opposite orientations of the intracellular Ca 2+ gradient and the external stimulus gradient suggest that more than one chemoattr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 47 publications
1
42
1
Order By: Relevance
“…Ca 2 + as a Second Messenger A [Ca 2 +]i increase controls widely different cellular processes, such as activation of some cytosolic enzymes (Schulman, 1998), gene transcription (Bito et al, 1997;Hardingham et al, 1997: Chawla andBading, 1998;Deisseroth et al, 1998), fertilization (Galione et al, 1993a;Lee et aI., 1993;Marchant and Parker, 1998), cell proliferation and differentiation (Berridge, 1995;Archer et al, 1998), apoptosis (Jayaraman and Marks, 1998), cell contraction (Meissner, 1994;Liu et aI., 1997), photoreception (Berridge, 1997), intracellular membrane fusion (Peters and Mayer, 1998), exocytosis, including neurotransmitter release (Lindau et al, 1992;Neher and Zucker, 1993;Regehr and Atluri, 1995;Henkel and Almers, 1996;Huang and Neher, 1996;Berridge, 1998;Kasai, 1999), endocytosis (Artalejo et al, 1995;Henkel and Almers, 1996), phagocytosis (Kruskal and Maxfield, 1987;Randriamampita et al, 1991;Ohmer-Schrock et al, 1995), amoeboid movement (Gilbert et al, 1994), and ciliary beat regulation (Lansley and Sanderson, 1999). For reviews, see Berridge (1997), Berridge et al (1998), and Verkhratsky and Toescu (1998).…”
Section: General Overview Of Ca 2 + Regulation In Eukaryotic Cellsmentioning
confidence: 99%
“…Ca 2 + as a Second Messenger A [Ca 2 +]i increase controls widely different cellular processes, such as activation of some cytosolic enzymes (Schulman, 1998), gene transcription (Bito et al, 1997;Hardingham et al, 1997: Chawla andBading, 1998;Deisseroth et al, 1998), fertilization (Galione et al, 1993a;Lee et aI., 1993;Marchant and Parker, 1998), cell proliferation and differentiation (Berridge, 1995;Archer et al, 1998), apoptosis (Jayaraman and Marks, 1998), cell contraction (Meissner, 1994;Liu et aI., 1997), photoreception (Berridge, 1997), intracellular membrane fusion (Peters and Mayer, 1998), exocytosis, including neurotransmitter release (Lindau et al, 1992;Neher and Zucker, 1993;Regehr and Atluri, 1995;Henkel and Almers, 1996;Huang and Neher, 1996;Berridge, 1998;Kasai, 1999), endocytosis (Artalejo et al, 1995;Henkel and Almers, 1996), phagocytosis (Kruskal and Maxfield, 1987;Randriamampita et al, 1991;Ohmer-Schrock et al, 1995), amoeboid movement (Gilbert et al, 1994), and ciliary beat regulation (Lansley and Sanderson, 1999). For reviews, see Berridge (1997), Berridge et al (1998), and Verkhratsky and Toescu (1998).…”
Section: General Overview Of Ca 2 + Regulation In Eukaryotic Cellsmentioning
confidence: 99%
“…The mechanism by which H 2 O 2 induces cell migration, however, is not fully understood, although H 2 O 2 is known to affect a number of signalling pathways associated with cell migration, including Ca 2+ signalling (Prevarskaya et al, 2011;Tsai et al, 2014;Wei et al, 2012) and Lyn activation (Yoo et al, 2011). Multiple studies have shown that Ca 2+ plays a key role in the spatial and temporal regulation of the actin cytoskeleton and focal adhesions (Brundage et al, 1991;Gilbert et al, 1994;Prevarskaya et al, 2011;Tsai et al, 2014;Wei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ca Cell signaling is the fundamental strategy by which cells respond to extracellular stimuli. Intracellular distribution of cell signaling is considered to be an important factor affecting the manner in which cells respond to extracellular stimuli with spatial specificity (1,2). Although little is known of the spatial aspect of cell signaling, that of Ca 2ϩ signaling visualized by Ca 2ϩ microscopy is presently the best characterized example.…”
mentioning
confidence: 99%
“…To address this issue, we visualized site-specific phosphorylation of vimentin by CaMKII 1 and Ca 2ϩ signaling in the same astrocytes. CaMKII is located downstream of Ca 2ϩ signaling and is thought to regulate various cellular responses (11,12).…”
mentioning
confidence: 99%